2022
DOI: 10.1126/sciadv.abg6711
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive long-read isoform analysis platform and sequencing resource for breast cancer

Abstract: Tumors display widespread transcriptome alterations, but the full repertoire of isoform-level alternative splicing in cancer is unknown. We developed a long-read (LR) RNA sequencing and analytical platform that identifies and annotates full-length isoforms and infers tumor-specific splicing events. Application of this platform to breast cancer samples identifies thousands of previously unannotated isoforms; ~30% affect protein coding exons and are predicted to alter protein localization and function. We perfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 65 publications
6
27
0
Order By: Relevance
“…Moreover, the cancer-specific SEs identified by long-read sequencing in breast cancer also showed the same length bias (fig. S1B), further confirming the length-dependent splicing changes in cancer (22). Together, our results revealed a previously unnoticed feature of splicing alteration in cancer, in which the short exons are more sensitive to be dysregulated regardless of the cancer types, analytic pipelines, and patient populations.…”
Section: Significant Length Biases In Cancer-associated Alternative E...supporting
confidence: 80%
“…Moreover, the cancer-specific SEs identified by long-read sequencing in breast cancer also showed the same length bias (fig. S1B), further confirming the length-dependent splicing changes in cancer (22). Together, our results revealed a previously unnoticed feature of splicing alteration in cancer, in which the short exons are more sensitive to be dysregulated regardless of the cancer types, analytic pipelines, and patient populations.…”
Section: Significant Length Biases In Cancer-associated Alternative E...supporting
confidence: 80%
“…Using the same approach, another study also reported 17 to 55% of novel isoforms in human breast cancer samples (Veiga et al, 2022). These studies, together with ours, indicate long-read sequencing is better approach for discovering novel isoforms and being able to better annotate animal genomes.…”
Section: Discussionsupporting
confidence: 69%
“…The human genome is considered to be better-annotated than farm animals’, while 36.4% of full-length transcripts identified by long-read Iso-Seq methods are classified as “novel” in human cortex tissue (Leung et al, 2021). Using the same approach, another study also reported 17 to 55% of novel isoforms in human breast cancer samples (Veiga et al, 2022). These studies, together with ours, indicate long-read sequencing is better approach for discovering novel isoforms and being able to better annotate animal genomes.…”
Section: Discussionmentioning
confidence: 93%
“…5d]. We verified that isoforms containing the deleted exon are expressed in a recent dataset comprised of 30 breast cancer samples 67 . Additionally, this deletion spans six regulatory elements annotated in the Open Regulatory Annotation dataset 68 .…”
Section: Temrs Contribute To Variation In Functional Regions Of Human...mentioning
confidence: 90%